ANALYSIS OF ASCETICISM AS A RELIGIOUS PHENOMENON (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The ascetic phenomenon, which has existed in the life of society since ancient times, has become an important and sometimes dominant factor in social development. In the twenty-first century it is impossible not to notice the rapid growth of countless associations, organizations, groups and individuals, which directly or indirectly reflect the attachment to the spread of" traditional "and" modern " mystical or mystical-ascetic systems. This article examines the phenomenon of asceticism in the traditions of World Religions in the field of religious phenomenology, which is one of the branches of religious studies.